`\frac{3mn}{-2p}` when `m\ =\ \frac{1}{3},` `n\ =-3,`and `p=3.`

1 answer

Substituting the given values, we have:

\[\frac{3mn}{-2p} = \frac{3\left(\frac{1}{3}\right)(-3)}{-2(3)} = \frac{-1\cdot(-3)}{-2\cdot3} = \frac{3}{6} = \boxed{\frac{1}{2}}.\]
Similar Questions
    1. answers icon 1 answer
    1. answers icon 1 answer
    1. answers icon 1 answer
  1. Let $a,$ $b,$ $c$ be complex numbers such that\begin{align*} \frac{a}{b + c} + \frac{b}{c + a} + \frac{c}{a + b} &= 0, \\
    1. answers icon 1 answer
more similar questions